The Importance Of Artificial Intelligence In Developing Students’ Algorithmic Thinking Skills (Journal of Pedagogical Inventions and Practices, 2025)
This paper examines the significant role of artificial intelligence (AI) in enhancing algorithmic thinking skills among students. By integrating AI technologies into educational practices, learners are exposed to sophisticated problem-solving techniques and logical reasoning frameworks. The study explores theoretical foundations, reviews recent scholarly research, and offers practical strategies for educators to foster computational creativity and critical thinking in classroom settings.